CANVAS BUSINESS MODEL USAGE TO INCREASE THE INCOME AND WELL BEING OF FAMILY IN THE KAPUAS RIVER COASTAL - Asma, Nurlia (Universitas Muhammadiyah Pontianak, 2024)
This study aims to determine whether the existence of a caping crafts business model canvas in Mendawai Village can support the well-being of the people of Mendawai Village. This research method uses a descriptive qualitative research method approach, which is a data collection technique that includes observation, interviews, and documentation to obtain information related to the management of the Business Model Canvas of caping crafts in Mendawai Village. The results showed that the Business Model Canvas, as a whole, was working well and was able to support the welfare of the bonnet craftsmen in Mendawai village. From the business activities carried out, the artisans feel that the results obtained are very sufficient to support their daily needs. Most of them can make a good living from selling Tudung handicrafts.